1998
DOI: 10.1093/ajcn/68.5.1028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different dietary cholesterol concentrations on lipoprotein plasma concentrations and on cholesterol efflux from Fu5AH cells

Abstract: Background:The fatty acid composition of the diet can modulate the effect of dietary cholesterol on plasma lipoproteins. However, HDL composition and its capacity to promote cholesterol efflux can be influenced by the diet. Objective: Modifications in plasma lipids and in the capacity of serum to stimulate the cholesterol efflux induced by a low-fat diet [National Cholesterol Education Program (NCEP) Step I diet], by a monounsaturated fatty acid (MUFA)-rich diet, and by addition of cholesterol to both diets w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…However, dietary saturated fat and cholesterol amount do not appear to affect cholesterol efflux to plasma in most of the studies conducted in humans [22][23][24] and animals. 37,38 Our in vitro cellular cholesterol efflux results were more comparable to those reported by Blanco-Molina et al 20 where the ability of serum to promote cholesterol efflux was slightly greater in 14 human subjects after a low-fat, high-cholesterol diet compared with the low-fat diet alone. Our results are also consistent with the reported HFHC diet-mediated effects on HDL-C and cholesterol efflux from macrophages and liver ABCG1 expression in mice.…”
Section: Discussionsupporting
confidence: 87%
“…However, dietary saturated fat and cholesterol amount do not appear to affect cholesterol efflux to plasma in most of the studies conducted in humans [22][23][24] and animals. 37,38 Our in vitro cellular cholesterol efflux results were more comparable to those reported by Blanco-Molina et al 20 where the ability of serum to promote cholesterol efflux was slightly greater in 14 human subjects after a low-fat, high-cholesterol diet compared with the low-fat diet alone. Our results are also consistent with the reported HFHC diet-mediated effects on HDL-C and cholesterol efflux from macrophages and liver ABCG1 expression in mice.…”
Section: Discussionsupporting
confidence: 87%
“…However, the results of many clinical trials have shown no correlation between egg consumption and the serum cholesterol concentration. [3][4][5][6] An epidemiological survey has fact in shown a negative correlation between the intake of eggs and cardiovascular diseases. 7) Thus, it is thought that a component in egg may help in controlling the serum cholesterol concentration.…”
mentioning
confidence: 99%
“…Furthermore, several studies have confirmed that the concentration of Lp A-I and Lp A-I:AII particles changes when the fatty acid composition of the diet is modified (28,29). On the other hand, the results of several studies of the effect of dietary fatty acid composition on serum capacity to promote cellular cholesterol efflux are still controversial (30)(31)(32)(33).In the present study, a long-term diet rich in vegetables, fruit, fish, and oils was administered to a healthy population. Different diets were created by varying the fatty acid saturation grade to study the effect on the plasma lipid and lipoprotein particle profile.…”
mentioning
confidence: 99%
“…Furthermore, in the women, the sera obtained after the consumption of diets with a high nϪ6 PUFA content also showed significantly more cholesterol efflux than did sera drawn during the SFA and MUFA phases. Although several studies (30)(31)(32)(33)48) recently investigated the effect of dietary fat type on cholesterol efflux, the results do not agree, and this important issue remains to be clarified.Gillotte et al (32) performed a detailed study in primates of the possible effects of diets differing in degree of saturation. They concluded that all diets produce HDL of the same fluidity and size with an identical capacity to promote cellular cholesterol efflux.…”
mentioning
confidence: 99%